Safety of Tonsillectomy and/or Adenoidectomy in Pediatric Patients with Prolonged Activated Partial Thromboplastin Time and Factor XII Deficiency - Du J; Gu QL; Lu YX; Zhang L; Zhan XJ; Wang Z (Dove Medical Press, 2024)
Jun Du,1 Qing-long Gu,1 Ying-xia Lu,1 Lei Zhang,2 Xiao-jun Zhan,1 Zhan Wang1 1Department of Otolaryngology, Head and Neck Surgery, Children's Hospital Capital Institute of Pediatrics, Beijing, 100000, People's Republic of China; 2Department of Hematopathology, Children's Hospital Capital Institute of Pediatrics, Beijing, 100000, People's Republic of ChinaCorrespondence: Qing-long Gu, Department of Otolaryngology, Head and Neck Surgery, Children's Hospital Capital Institute of Pediatrics, No. 2 Yabao Road, Chaoyang District, Beijing, 100020, People's Republic of China, Tel +86-13810091816, Email qinglonggugql@126.comObjective: To evaluate the safety and feasibility of tonsillectomy and/or adenoidectomy (T&A) in pediatric patients with prolonged activated partial thromboplastin time (APTT) and coagulation factor deficiency.Methods: A prospective study was admitted to the children undergoing T&A at our institution between October 2019 and January 2020, specifically focusing on preoperative coagulation function. Within this group, we identified 5 patients exhibiting prolonged APTT and coagulation factor deficiencies, constituting the experimental group, and 10 patients matched by gender and age with normal blood coagulation function were selected as the control group. Comparative analyses between the two groups were conducted, focusing on surgical duration, intraoperative bleeding volume, duration of hospital stay, and postoperative complications such as active bleeding across the groups. At the six-month postoperative mark, a reassessment of coagulation functions and factor assays was conducted within the experimental group.Results: No statistically significant differences were discovered in terms of surgical duration or bleeding volume when comparing the experimental subgroups with their respective control counterparts. Furthermore, there were no incidences of postoperative active bleeding observed in any of the groups. Notably, postoperative APTT values (32.7 ± 1.7s) exhibited a significant disparity compared to preoperative levels (43.7 ± 1.8s, p < 0.01). Coagulation factors demonstrated normalization, evidenced by a significant difference in postoperative Factor XII levels (40.2 ± 5.4%) compared to preoperative levels (63.1 ± 5.9%, p < 0.01).Conclusion: Prolonged APTT with FXII factor deficiency does not show a significant bleeding tendency and is not a contraindication for T&A surgery. Post T&A surgery, children with abnormal coagulation function and deficient clotting factors show significant improvement compared to pre-surgery. It is important to consider that chronic inflammation in adenoids and tonsils may contribute to the prolongation of APTT and the manifestation of Factor XII deficiency.Keywords: adenoidectomy, children, factor XII deficiency, prolonged APTT, tonsillectomy